(untitled) (Journal of Imam Al-Kadhim College, 2023)
The Eurasian Orientation has given a significant role to the Russian Foreign Policy in its foreign orientation, especially with the Eurasian doctrine that guides this policy. The emergence of this doctrine was the result of gradual process started from the dissolution of the Soviet Union until the arriving of Vladimir Putin to the presidency of Russia in 2000 despite of the Eurasian doctrine roots in its classical form date back to the beginning of twentieth century. The emergence of the new Eurasian as a geopolitical orientation, Alexander Dugin considers as one its distinguished thinkers, dominates the drawing up and implement of the Russian Foreign Policy, which formed a significant geopolitical philosophy distinct from what prevailing in the east and west and as a competitor to the other theories and insights. That it gives a special identity to the Russian foreign policy and contributes to the development of the Russian role regionally and internationally.